International Technical Lectures Collaboration (IILC) session between Civil Engineering Studies, Universiti Teknologi Pulau Pinang Branch, Malaysia and The Department of Civil Engineering, Universitas Malikussaleh, Indonesia / Syahrul Fithry Senin, Khairullah Yusuf and Maizuar Maizuar - Senin, Syahrul Fithry; Yusuf, Khairullah; Maizuar, Maizuar (UiTM Global @ Office of International Affairs, 2024)
Abstract: This article elucidates an international academic collaboration between the Civil Engineering Studies at the College of Engineering, Universiti Teknologi MARA (UiTM) Pulau Pinang Branch, Malaysia, and its Memorandum of Understanding (MoU) partner, the Department of Civil Engineering, Universitas Malikussaleh (UNIMAL), Aceh, Indonesia. This endeavour was undertaken as part of a series of academic lecture sessions between the two institutions throughout2023.